Effect of Lymphocyte Subsets on Bone Density in Senile Osteoporosis: A Retrospective Study - Cong Peng; Zongwei Guo; Yue Zhao; Rui Li; Liang Wang; Wenping Gong (Journal of Immunology Research)
Background. Several studies have shown that lymphocyte subsets can mediate the occurrence of osteoporosis (OP); however, the predictive ability of lymphocyte subsets in senile OP has not been elucidated. Purpose. To investigate the ability of lymphocyte subsets to predict senile osteoporosis (OP). Methods and Materials. This study included 44 patients with senile OP and 44 without OP. Dual-energy X-ray absorptiometry (DEXA) was used to determine bone mineral density (BMD). Flow cytometry was used to analyze the absolute counts of the lymphocyte subsets and cytokine levels. Finally, the correlation between BMD and lymphocyte subset counts in the two groups was analyzed. Results. There were no significant differences in age, sex, or weight between the OP and non-OP groups. The absolute counts of total T lymphocytes and CD8+ T lymphocytes in the OP group were significantly lower than those in the non-OP group. The levels of IFN-γ or TNF-α in the OP group were significantly higher or lower, respectively, than those in the non-OP group. PCA showed that age, BMI, total T lymphocytes, CD4+ T lymphocytes, CD8+ T lymphocytes, and B lymphocytes were the principal components of senile OP. The linear regression equation showed that BMD of the right femoral neck significantly decreased with a decline in CD8+ T lymphocyte counts. Conclusion. BMD decreased with a decrease in CD8+ T lymphocytes. The mechanism by which lower lymphocyte subsets lead to lower BMD may be related to abnormal bone metabolism caused by immune aging. Therefore, we considered that CD8+ T lymphocytes could be used to predict the incidence of senile OP.